Russian demand for dietary quality: Nutrition transition, diet quality measurement, and health investment theory - Christine Burggraf (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2017)
[Study Objectives] This thesis aims to contribute interdisciplinary findings, which benefit from both economic and nutritional approaches, that explain the Russian dietary quality with respect to nutrient deficiencies, but also the increasing prevalence of nutrition-related chronic diseases. Thereby, the main objective of this study is an empirical analysis of Russian dietary quality, as well as its socio-economic, sociodemographic, and lifestyle-influencing factors. Based on this main objective, the following specific sub-objectives are derived that aim to answer the aforementioned relevant research questions of this thesis. After clarifying the macroeconomic conditions of food demand, the first sub-objective of this thesis is the empirical analysis of trends in Russian food consumption patterns during economic transition. Thereby, it is necessary to consider specific features of Russian food consumption before and after the collapse of the Soviet system such as cultural aspects, food availability, household food consumption budgets, and nutritional education. The second sub-objective of this study is the development of a composite index to measure dietary quality, which must be explicitly suitable for the analysis of Russian dietary quality. Such a composite index regarding the measurement of dietary quality needs to take into account both the evidenced specifics of Russian dietary patterns, as well as the data restrictions of the employed data set. The respective empirical analysis of this study is supposed to establish if and to what extent dietary quality has changed during the Russian transformation process. The third sub-objective of this thesis is to analyze the Russian demand for dietary quality using a comprehensive theoretical framework; GROSSMAN's dynamic health investment model provides such an economic framework. However, in order to employ this model for the analysis of dietary quality, this thesis aims at the following two model modifications: first, a change of the specification of the model's inherent health investment production function in order to receive more realistic model implications, and second, the model's adaption to the analysis of the demand for dietary quality. Based on such a modified health investment model, demand functions shall be derived that describe the optimum demand for dietary quality depending on relevant socio-demographic, socio-economic, and lifestyle factors. Afterwards, these theoretically implied relationships between the demand for dietary quality and its influencing factors shall be empirically employed to explain the demand for dietary quality in Russia. The theoretical and empirical findings of the Russian analysis of dietary quality lead to the fourth sub-objective, which is to provide important suggestions regarding nutrition policy. Identified problematic profiles in the Russian diet, as well as their influencing factors, shall be the basis for designing appropriate educational or market-specific intervention programs, which must be aimed at achieving a healthier Russian diet. Owing to the increased prevalence of nutrition-related diseases and the associated healthcare costs within the Russian population, such official intervention strategies are of tremendous socio-political interest.
urn:nbn:de:gbv:3:2-86076
Keywords: 330